No Differences Between 12 Weeks of Block- vs. Traditional-Periodized Training in Performance Adaptations in Trained Cyclists - Almquist, Nicki Winfield; Eriksen, Hanne Berg; Wilhelmsen, Malene; Hamarsland, Håvard; Ing, Steven; Ellefsen, Stian; Sandbakk, Øyvind; Rønnestad, Bent R.; Skovereng, Knut (Frontiers in Physiology, 2022)
The purpose of this study was to compare the effects of 12 weeks load-matched block periodization (BP, n=14), using weekly concentration of high- (HIT), moderate- (MIT), and low- (LIT) intensity training, with traditional periodization (TP, n=16) using a weekly, cyclic progressive increase in training load of HIT-, MIT-, and LIT-sessions in trained cyclists (peak oxygen uptake: 58±8 ml·kg-1·min-1). Red blood cell volume increased 10±16% (p=0.029) more in BP compared to TP, while capillaries around type I fibres increased 20±12% (p=0.002) more in TP compared to BP from Pre to Post12. No other group differences were found in time-trial (TT) performances or muscular-, or haematological adaptations. However, both groups improved 5-min and 40-min TT power by 9±9% (p<0.001) and 8±9% (p<0.001), maximal aerobic power (Wmax) and power output at 4 mmol·L-1 blood lactate (W4mmol), by 6±7 (p=0. 001) and 10±12% (p=0.001), and gross efficiency (GE) in a semi-fatigued state by 0.5±1.1%-points (p=0.026). In contrast, GE in fresh state and VO2peak were unaltered in both groups. The muscle protein content of -hydroxyacyl (HAD) increased by 55±58% in TP only, while both TP and BP increased the content of cytochrome c oxidase subunit IV (COXIV) by 72±34%. Muscle enzyme activities of citrate synthase (CS) and phosphofructokinase (PFK) were unaltered. TP increased capillary-to-fibre ratio and capillary around fibre (CAF) type I by 36±15% (p<0.001) and 17±8% (p=0.025), respectively, while BP increased capillary density (CD) by 28±24% (p=0.048) from Pre to Post12. The present study shows no difference in performance between BP and ”best practice”-TP of endurance training intensities using a cyclic, progressively increasing training load in trained cyclists. However, haematological and muscle capillary adaptations may differ.